Influência do espaçamento de plantio e idade de colheita na qualidade da madeira de eucalipto para celulose - Feuchard, Lairo David (2015)
The genus Eucalyptus has become in Brazil an important source of raw material for the various forest-based industries. Eucalyptus plantations reached in 2013 planted area of 7.6 million hectares, with 2.8% growth over the previous year. The objective of this study was to evaluate the influence of different planting spacing (3x1, 3x2, 3x3 and 3x4 m) and two ages (4 and 5 years) in the quality of Eucalyptus clones urophylla x Eucalyptus grandis. The clones used in the research were planted to meet the pulp and paper industry. Anatomical studies were conducted, chemical, basic density and sapwood/heartwood relationship of wood. The basic wood density increased with the planting spacing and cutting age of 4 to 5 years. Extractives soluble in acetone levels differ in relation to the planting spacing, as well as the age cutting. The total lignin content showed an increasing trend with increasing of spacing. In the anatomical study, the tangential diameter and frequency of vessels showed an increase with the age. In general statistical difference was observed for the length of the fibers in different spacing checking increased with the increase of planting area and similar to the behavior was observed to fraction and wall thickness values. The sapwood/heartwood ratio tended to increase with increasing spacing coming to present increase of over 200% of lowest to highest spacing of planting.